Rate variation in the evolution of non-coding DNA associated with social evolution in bees. (22nd July 2019) - Rubin, Benjamin E. R.; Jones, Beryl M.; Hunt, Brendan G.; Kocher, Sarah D.
Abstract : The evolutionary origins of eusociality represent increases in complexity from individual to caste-based, group reproduction. These behavioural transitions have been hypothesized to go hand in hand with an increased ability to regulate when and where genes are expressed. Bees have convergently evolved eusociality up to five times, providing a framework to test this hypothesis. To examine potential links between putative gene regulatory elements and social evolution, we compare alignable, non-coding sequences in 11 diverse bee species, encompassing three independent origins of reproductive division of labour and two elaborations of eusocial complexity. We find that rates of evolution in a number of non-coding sequences correlate with key social transitions in bees. Interestingly, while we find little evidence for convergent rate changes associated with independent origins of social behaviour, a number of molecular pathways exhibit convergent rate changes in conjunction with subsequent elaborations of social organization. We also present evidence that many novel non-coding regions may have been recruited alongside the origin of sociality in corbiculate bees; these loci could represent gene regulatory elements associated with division of labour within this group. Thus, our findings are consistent with the hypothesis that gene regulatory innovations are associated with the evolution of eusociality and illustrate how a thorough examination of both coding and non-coding sequence can provide a more complete understanding of the molecular mechanisms underlying behavioural evolution. This article is part of the theme issue 'Convergent evolution in the genomics era: new insights and directions'.